Intravenous immunoglobulin, splenectomy, and antibiotic prophylaxis in Wiskott-Aldrich syndrome. Issue 5 (November 1996) - Litzman, J; Jones, A; Hann, I; Chapel, H; Strobel, S; Morgan, G
Abstract : AIM: To assess the results of supportive treatment with intravenous immunoglobulin (IVIG) and antibiotic prophylaxis in combination with splenectomy in patients with Wiskott-Aldrich syndrome. STUDY DESIGN: Retrospective review of case records of 21 patients from March 1984 to February 1996. RESULTS: Thrombocytopenia was cured in 14 of 15 patients who had splenectomy, but it recurred intermittently in three. Mean platelet volume (MPV) was normal transiently in some patients, but all MPV values were subnormal 8-23 months after splenectomy. Antibiotic and IVIG prophylaxis may have contributed to the lack of a detectable increase in the number of severe acute bacterial infections in the 451 months after splenectomy. Four patients died in 2205 months of observation before and after splenectomy (median 82, range 16-248): two of cerebral B cell lymphoma, one of progressive multifocal leucoencephalopathy, and one with severe chronic chest disease of pneumonia. CONCLUSION: Adequate supportive treatment with IVIG and antibiotic prophylaxis together with splenectomy enables good survival and quality of life in the short and medium term in patients with Wiskott-Aldrich syndrome. Persistence of infection, bleeding, and vasculitic and allergic symptoms in a significant minority and the risk of development of lymphoma, however, suggest that bone marrow transplantation may be indicated if an HLA identical donor is available.